1993
DOI: 10.1128/aem.59.5.1573-1578.1993
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of a Protease Involved in the Processing of a Streptomyces reticuli Cellulase (Avicelase)

Abstract: A 36-kDa protease from Streptomyces reticuli had recently been shown to be responsible for the in vivo and in vitro processing of the 82-kDa cellulase (Avicelase) Cel-1 from S. reticuli to a 42-kDa truncated enzyme. It was induced only in the presence of Avicel, hydroxyethylcellulose, and xylan. The addition of the nonionic detergent Tween 80 to the culture medium containing Avicel as the carbon source led to a 10-fold increase in extracellular proteolytic activity. The protease, which has an isoelectric point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 22 publications
(27 reference statements)
0
9
0
1
Order By: Relevance
“…The binding domain targets the enzyme to Avicel during early stages of growth. After this, the C-terminal 42-kDa region is released by a 36-kDa metalloprotease (Moormann et al, 1993). The 42 kDa form hydrolyses Avicel to oligomers that are further processed to cellobiose and cellotriose by a glucosidase (Schlochtermeier et al, 1992a).…”
Section: Degradation Of Crystalline Cellulosementioning
confidence: 99%
“…The binding domain targets the enzyme to Avicel during early stages of growth. After this, the C-terminal 42-kDa region is released by a 36-kDa metalloprotease (Moormann et al, 1993). The 42 kDa form hydrolyses Avicel to oligomers that are further processed to cellobiose and cellotriose by a glucosidase (Schlochtermeier et al, 1992a).…”
Section: Degradation Of Crystalline Cellulosementioning
confidence: 99%
“…Earlier we had shown that, in the course of cultivation, one extracellular S. reticuli protease specifically cleaves the cellulase (Avicelase). Thus a truncated cellulase not containing the binding domain is released to the culture filtrate (Schlochtermeier et al, 1992a,b;Moormann et al, 1993). Similarly the substrate-bound 59-kDa chitinase is specifically proteolytically processed to a 47-kDa truncated form which diffuses into the culture filtrate.…”
Section: Streptomyces Olivaceoviridis and Transformants Of Variousmentioning
confidence: 99%
“…Avicelase consists of a Cterminal catalytic domain belonging to the family E (4,11), one central domain of an as-yet-unknown function, and an N-terminal substrate-binding domain. In the course of cultivation, the strain produces an extracellular 36-kDa protease (9) which processes Avicelase to a truncated, catalytically active 42-kDa enzyme lacking the cellulose-binding domain and the central part of the progenitor enzyme (11). Several Streptomyces strains acquire the ability to degrade crystalline cellulose if they are transformed with the plasmid pZV1.…”
mentioning
confidence: 99%